ANALISIS PENGARUH PERTUMBUHAN EKONOMI DAN PENGELUARAN PEMERINTAH ACEH TERHADAP PENDAPATAN ASLI DAERAHPROVINSI ACEH SETELAH TSUNAMI - Hewi Susanti; Mohd Nur Syechalad; Abubakar Hamzah (Syiah Kuala University, 2017)
This study aimed to determine the effect of economic growth and government expenditure of Aceh on revenue (PAD) province of Aceh after the tsunami. The data used in this research are secondary data obtained from the Central Statistics Agency (BPS) of Aceh Province. The method used to analyze data is the method of least squares (OLS) with linear regression models. Variable PAD research is the province of Aceh (Y) as the dependent variable and economic growth (X1), and government expenditures of Aceh (X2) as independent variables. Based on the survey results revealed that the variables X1 and X2 positive and significant impact on Y at the level of α = 0.10 and α = 0.01. While it simultaneously independent variables have a significant effect on the level of α = 0.01. Variation in the dependent variable explained by the independent variable capable of amounting to 82.90 percent. The estimation results of the model indicate that if all the variables are zero then the PAD province of Aceh after the tsunami (Y) amounted to 1,442 billion rupiah; if economic growth (X1) grew by 1 percent would increase by 0,016 percent y; if expenditure on governent of Aceh (X2) increase by 0,388 percent Y. Goverment of Aceh needs to increase the rate of economic growth in the province of Aceh by giving special attention to the leading sectors and potential to be developed in the province of Aceh is expected to increase the amount of revenue the Province of Aceh.